Response of Local Garlic on Solid and Liquid Vermicompost and The Impact to Financial Yield - Kristina, Nilla; Firmawini, Elvina; Resigia, Elara (Kadiri University - Faculty of Agriculture, 2025)
Converting solid Vermicompost into liquid form is an alternative for garlic cultivation in the Dibawah Lake Solok region, and the cost is cheaper. A preliminary study evaluated the impact of applying solid Vermicompost (0, 5, 10, and 15 t/ha) on garlic growth and yield. A subsequent study examined the effect of applying solid Vermicompost in liquid form using a chitosan solution and identified effective NPK fertilizer doses to optimize local garlic growth and yield. The experimental design was a randomized factorial with NPK doses of 0, 100, and 200 kg/ha and Vermicompost concentrations of 0, 30, 60, or 90 g/L chitosan solution. The preliminary study demonstrated that applying 10 to 15 tons per hectare of solid Vermicompost combined with 100 kilograms per hectare of NPK fertilizer significantly increased garlic yield compared to no solid Vermicompost application. A subsequent study found that varying NPK doses from 0 to 200 kilograms per hectare and Vermicompost from 0 to 90 grams produced similar effects on local garlic growth and yield. However, yields remained lower than those achieved with 15 tons per hectare of solid Vermicompost. In contrast, substituting solid with liquid Vermicompost at all tested concentrations resulted in higher profitability than the 15 tons per hectare solid Vermicompost treatment, particularly for 100 NPK and 60 grams of Vermicompost in chitosan solution. That treatment was more cost-effective for farmers because it increased income by 63% and was more environmentally friendly than the solid form application in the Dibawah Lake Solok region.